SUSTAINABLE TOURISM AS A TOOL FOR ENVIRONMENTAL CONSERVATION AND CLIMATE CHANGE ADAPTATION - Boiko, Viktoriia (SWorld-Ger Conference proceedings, 2024)
The paper examines the role of sustainable and ecological tourism in the preservation of natural resources and the fight against climate change. The principles of ecological tourism are analyzed, highlighting their contribution to biodiversity conservatio